Emberley on Hot Button Politics in Canada’s Universities: A Critique - Carson, A. Scott (Canadian Journal of Higher Education, 2017)
In his recent book, Zero Tolerance: Hot Button Politics in Canada s Universities (1996), Richard Emberley attacks the government, business community, university administrators, magazine publishers and acade- mics for their complicity in pushing Canadian universities to the point of ruin. His accusation is that academe is pressed to achieve so many social, political and economic objectives that it risks not being successful in any of them. He provides a number of recommendations for restructuring higher education and these are presented in the context of a very rich con- ception of what a university should be. This paper examines Emberley's account of universities and the "scholarly culture" which has developed since the 13th century. It is argued that Emberley has an overly narrow view of the role of a university and one that is based on certain mistaken presumptions about what constitutes value in education.